High-grade mixed neuroendocrine non-neuroendocrine neoplasm of the gastroesophageal junction: A rare case report and review of literature - Mohamed Sulaiman; Shipra Agarwal; Amitabha Mandal; Sunil Kumar; Prasenjit Das (Wolters Kluwer Medknow Publications, 2022)
Mixed neuroendocrine non-neuroendocrine neoplasm (MiNeN) is a recently described entity of the esophagus in the latest (fifth) edition of WHO Classification of Digestive System Tumors. It is often a difficult pathological diagnosis, especially in small preoperative biopsies. We herein report a case of high-grade MiNeN of gastroesophageal junction diagnosed as a squamous cell carcinoma in preoperative biopsy and subsequently as a high-grade MiNeN in esophagogastrectomy specimen comprising areas of mucoepidermoid carcinoma and large-cell neuroendocrine carcinoma (NEC). This report accentuates the importance of deeper multisite preoperative biopsies as the management is completely different in a MiNeN from esophageal squamous cell carcinoma.